Quando o bar se torna estádio: um estudo acerca do torcer em bares de Belo Horizonte - Felipe Vinicius de Paula Abrantes (2015)
This paper has the objective of identifying how the support for the football teams Clube Atlético Mineiro and Cruzeiro Esporte Clube occur in pubs in the city of Belo Horizonte. For this purpose, we appealed to the soccer fans that were in the pubs in days of matches and to the owners of the pubs. These pubs, as well as football and the supporters of football teams, are very important for leisure purposes of a significant parcel of the Brazilian population. In a special way in Belo Horizonte, which has in its pubs one of the most important touristic and cultural references, being considered the capital of pubs. In football, the city has two clubs with a considerable amount of fans and with a good performance in the national sport scenario, Atlético and Cruzeiro and also for this reasons this paper made the analysis of the supporting in matches of these two institutions. Regarding the research methodology, it was chosen the observation of the participants, annotations of the matches in a notebook realized in 2014 and in the first games of 2015 appliance of questionnaires with the soccer fans, totalizing 75, and semi-structured interviews with four soccer fans and four owners of pubs. The data collected allow us to state that watching soccer games is a very recurrent and important practice for a considerable amount of soccer fans in these pubs. It also allowed us to identify the different forms in which this support happens. The pubs, apart from being a space that allows the supporters to watch the games and a manifestation of the sense of belonging in a soccer club, also show themselves as a locus keen to narrowing links, creating bonds, friendships and sociability among the subjects that choose to be in that space supporting their soccer clubs. Other results obtained also explain relevant information, such as: which are the common characteristics of these supporters, the importance of the consumption of alcohol for the practice of supporting the soccer clubs, which factors leads to supporting the soccer clubs in a pub, and the economical impact that the transmission of the matches have for the profit of the commerce. It becomes clear that the cultural paper played by the pubs in the city of Belo Horizonte and how these forms of leisure, such as the supporting of the football teams, can be diverse and be linked with others spheres of culture and society.